DIPLOMASI BUDAYA INDONESIA MELALUI WAYANG KULIT DI AMERIKA SERIKAT - Lidya Desriyanti; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is about Indonesia diplomacy effort to introduce Wayang Kulit in United States. Wayang Kulit is an Indonesia cultural art that is unique and loved by adults and children. With the set of Wayang Kulit by UNESCO as Indonesia's cultural heritage, it is the responsibility of Indonesia to introduce Wayang Kulit to other countries. Wayang kulit is one of the steps to introduce Indonesia cultural to the United States, and this research aims to know the Efforts of Indonesia Diplomacy Through Wayang Kulit held in the United States.This study uses a neorealist perspective, which focuses on the state as the main actor in the international polytic system. Indonesia wants to introduce the art of Wayang Kulit cultural in the United States. To describe this research, the author uses the theory of cultural diplomacy. This research is qualitative, this research uses library research technique, where this research with data collection technique from book literature, magazine, newspaper, and visit to internet and other sources.The results of this study indicate that Indonesia made efforts through multi track diplomacy to introduce Wayang Kulit cultural in the United States through multi track Government, Non Government and private citizen, with the effort, Indonesia got the response by the United States community well.Keywords: Wayang Kulit, cultural heritage, multi track diplomacy, diplomacycultural